Synergistic Anticancer Effect of Peptide‐Docetaxel Nanoassembly Targeted to Tubulin: Toward Development of Dual Warhead Containing Nanomedicine. Issue 2 (26th October 2016) - Mohapatra, Saswat; Saha, Abhijit; Mondal, Prasenjit; Jana, Batakrishna; Ghosh, Subhajit; Biswas, Atanu; Ghosh, Surajit
Abstract : Microtubule dynamics play a crucial role in cancer cell division. Various drugs are developed to target microtubule. Although a few of them show potential in treatment of cancer, but success rate is limited due to their poor bioavailability and lack of specificity. Thus, development of highly bioavailable and target specific anticancer drug is extremely necessary. To address these key issues, here, a combination of approaches such as development of a dodecapeptide‐docetaxel nanoassembly targeted to tubulin and MUC1 (mucin 1, cell surface associated glycoprotein) targeting oligonucleotide aptamer conjugated liposome for delivering peptide‐docetaxel nanoassembly into the breast cancer cell have been demonstrated. These studies reveal that the peptide forms nanoassembly and entraps docetaxel drug. Further, the liposomal formulation of peptide‐docetaxel exerts synergistic anticancer effect, activates key mitotic check point proteins, and inhibits bipolar spindle formation, metastatic cancer cell migration, and growth of tumor mimicking 3D multicellular spheroid. Abstract : Cancer cell specific, MUC1 targeted oligonucleotide aptamer conjugated liposome containing a novel combination of peptide‐docetaxel nanoassembly targeted to tubulin is developed. This combination exerts synergistic anticancer effect, enhances docetaxel sensitivity, disrupts intracellular microtubule networks, activates key mitotic check point proteins, inhibits metastatic cancer cell migration, and significantly reduces the tumor mimicking 3D multicellular spheroid sizes.